Microstrip Patch Antenna Design with Artificial Magnetic Conductor (AMC) at 26 GHz - Othman, Zakyra Imana; Anuar Hamzah, Shipun; Ramli, Khairun Nidzam; Mohd Shah, Shaharil; Saiman, Suhaimi (Journal of Electronic Voltage and Application, 2021)
Advancements in 5G wireless communication systems are expected to enhance the communication capability significantly to achieve the higher data rate by accommodating broad bandwidth. In this paper, three compact sizes of rectangular microstrip patch antennas that were made of RT5880, FR-4 and RO3003 substrates with 0.5 mm thickness and resonating at 26 GHz were proposed for the 5G applications. However, the antenna having narrow bandwidth and low gain which contributes to drawback of this microstrip patch antenna design and hence an Artificial Magnetic Conductor (AMC) was proposed to overcome this drawback. The 3.5 mm ´ 3.5 mm rectangular loop-slot AMC was designed at 26 GHz using FR-4 and it is found that integrating the AMC structure to the printed patch antenna significantly improved the gain and directivity of the antenna. With the help of AMC design, for RT5880 patch antenna, the gain increased for approximately 5% from 6.04 dBi to 6.34 dBi. Besides that, RO3003 patch antenna gain improved for 78.62% from 4.77 dBi to 8.52 dBi and for FR-4 patch antenna, the gain escalated from 2.24 dBi to 7.86 dBi (roughly 251% increment). As a conclusion, the directivity of RT5880 substrate solely decreased for approximately 13.75%. Meanwhile for RO3003 and FR-4 patch antennas, with the assist from AMC design, the directivity of antenna escalated for more than 120 % compared to without AMC and this proved that this design has potential to be used for 5G wireless networks and applications.